2017
DOI: 10.3390/ijms18112367
|View full text |Cite
|
Sign up to set email alerts
|

Lignin from Micro- to Nanosize: Applications

Abstract: Micro- and nanosize lignin has recently gained interest due to improved properties compared to standard lignin available today. As the second most abundant biopolymer after cellulose, lignin is readily available but used for rather low-value applications. This review focuses on the application of micro- and nanostructured lignin in final products or processes that all show potential for high added value. The fields of application are ranging from improvement of mechanical properties of polymer nanocomposites, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(100 citation statements)
references
References 136 publications
(160 reference statements)
2
96
0
2
Order By: Relevance
“…There are numerous possibilities for converting lignin into chemicals and derivatives. One interesting approach to developing new materials is preparation of lignin particles, as reviewed by Beisl et al 121 and Bai et al 122 For example, alkaline lignin extracted from the residues resulting from furfural production is soluble in basic water. In acidic conditions, lignin becomes insoluble and forms particles that are an effective emulsifier for o/w Pickering emulsions.…”
Section: Regenerated Cellulosementioning
confidence: 99%
“…There are numerous possibilities for converting lignin into chemicals and derivatives. One interesting approach to developing new materials is preparation of lignin particles, as reviewed by Beisl et al 121 and Bai et al 122 For example, alkaline lignin extracted from the residues resulting from furfural production is soluble in basic water. In acidic conditions, lignin becomes insoluble and forms particles that are an effective emulsifier for o/w Pickering emulsions.…”
Section: Regenerated Cellulosementioning
confidence: 99%
“…In recent years, apart from its combustion for energy, isolation of lignin originating from industrial kraft pulping processes as well as biorefinery plants producing ethanol as biofuel has seen a steady increase. Parallel to the surge in the availability of lignin, nano‐ and microscaled lignin‐based materials and state‐of‐the‐art analytical techniques that provide a more detailed understanding of the structural differences of the various lignins were developed …”
Section: Introductionmentioning
confidence: 99%
“…In addition, lignin nanoparticles could decrease surface and interfacial tensions in mixtures of water and hydrophobic liquids and create stable Pickering emulsions . Some studies have also reported the use of lignin based products as antibacterial compounds and carbonized lignin nano fibres for energy storage in batteries …”
Section: Applicationmentioning
confidence: 99%
“…[103,104] Some studies have also reported the use of lignin based products as antibacterial compounds and carbonized lignin nano fibres for energy storage in batteries. [105,106]…”
Section: Lnp Usementioning
confidence: 99%